CMV pneumonitis in a patient with Crohn's disease taking azathioprine. Issue 4 (23rd April 2021) - Hawthorne, Timothy Zef; Shellien, Rachel; Chambers, Lucy; Devereux, Graham
Abstract : This case report discusses the rare presentation of cytomegalovirus (CMV) pneumonitis in a young patient with moderately severe Crohn's disease managed with low dose azathioprine. CMV pneumonitis was initially suspected on CT chest images and confirmed by PCR for CMV. She was treated with intravenous ganciclovir and later stepped down to oral valganciclovir. Although this patient had a prolonged and complicated hospital admission, a good clinical outcome was achieved. CMV infection was raised as an early differential and antiviral treatment was started without delay. This case study, therefore, makes the case for increased awareness of the possibility of, and recognition of CMV pneumonitis among healthcare professionals as a way of preventing significant morbidity and mortality. It also raises awareness of checking for slow metabolisers of azathioprine before initiation to look for individuals who may be at increased risk of azathioprine's adverse effects.